Examining Depression in Parkinson's Disease in Sociocultural Contexts: Moving from Stigma to Care - Farhat Yasmin Minhas; Junaid Rasool; Maryam Raza; Hafiz Muhammad Imtiaz Afzal; Iqbal, Saba; Sadia Chaudhary (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To estimate the prevalence of depression and to explore socio-demographic and clinical risk factors among tertiary-care patients with Parkinson's disease (PD) in Pakistan. METHODOLOGY: This cross-sectional analytical design study was conducted in the outpatient department (OPD) of a tertiary care medical facility (CMH), Lahore, from March to May 2023. Ninety-four consecutive idiopathic PD patients were recruited for the cross-sectional analytical study from CMH Lahore. The study utilized a self-report questionnaire and the Harvard Department of Psychiatry/National Depression Screening Day Scale (HANDS) to gather data on patients' age, sex, marital status, employment status, and disease duration. In the study, adult patients with idiopathic Parkinson's Disease without any severe medical conditions were included. RESULTS: The patients were 53 males and 41 females. The prevalence of depression in the study population was 39.36% (N 94). Most of the patients were diagnosed in the age group 51-60 years, and they were found to be more depressed than the younger patients. The most often reported symptoms of depression among individuals who were more depressed were low energy, trouble focusing or making decisions, feeling hopeless, feeling blue, and having trouble sleeping. All analyses were done on SPSS version 26.0 for Windows. CONCLUSION: In Parkinson's disease (PD), depression symptoms are prevalent, particularly in individuals with more severe cognitive impairment who are more likely to have or aggravate depression. Thus, it is equally important to identify and treat the disease along with any associated depression.